Therapeutic Effect of Ligustilide-Stimulated Adipose-Derived Stem Cells in a Mouse Thromboembolic Stroke Model. Issue 5 (May 2016) - Chi, Kang; Fu, Ru-Huei; Huang, Yu-Chuen; Chen, Shih-Yin; Lin, Shinn-Zong; Huang, Pi-Chun; Lin, Po-Cheng; Chang, Fu-Kuei; Liu, Shih-Ping
Stroke is a result of cerebral ischemia that triggers a cascade of both physiological and biochemical events. No effective treatment is available for stroke; however, stem cells have the potential to rescue tissue from the effects of stroke. Adipose-derived stem cells (ADSCs) are an abundant source of adult stem cells; therefore, ADSC therapy can be considered as a future strategy for regenerative medicine. However, more research is required to improve the effectiveness of transplanted ADSCs as a treatment for stroke in the mouse stroke model. Ligustilide, isolated from the herb Angelica sinensis, exhibits a protective effect on neurons and inhibits inflammation. We also demonstrated that ligustilide treatment increases the expression levels of homing factors such as SDF-1 and CXCR4. In the present study, we evaluated the therapeutic effects of ADSC transplantation and ligustilide treatment in a mouse thromboembolic stroke model by behavioral tests, including beam walking, locomotor activity, and rotarod analysis. ADSCs pretreated with ligustilide were transplanted into the brains of stroke mice. The results showed that the therapeutic effect of ADSCs pretreated with ligustilide was better than that of ADSCs without ligustilide pretreatment. There was no difference between the recovery of mice treated by ADSC transplantation combined with subcutaneous ligustilide injection and that of mice treated only with ADSCs. The TUNEL assay showed fewer apoptotic cells in the brains of mice transplanted with ADSCs pretreated with ligustilide as well as in those without pretreatment. In summary, pretreatment of ADSCs with ligustilide improves the therapeutic efficacy of ADSC transplantation. The results of this study will help improve stem cell therapies being developed for future clinical applications.